Primary squamous cell carcinoma of the ampulla of Vater: management and review of the literature. Issue 1 (7th January 2021) - Soni, Subhash; Elhence, Poonam; Varshney, Vaibhav Kumar; Suman, Sunita
Abstract : Squamous cell carcinoma (SCC) of the ampulla of Vater is a rare pathology and only few cases are reported in the literature. With limited experience of primary SCC in the ampulla of Vater, its biological behaviour, prognosis and long-term survival rates are not well known. A 38-year-old woman presented with a history of painless progressive jaundice for which self-expending metallic stent was placed 3 years back. She was evaluated and initially diagnosed as probably periampullary adenocarcinoma. She underwent pancreaticoduodenectomy and histopathology with immunohistochemistry was suggestive of SCC of ampulla of Vater. She received adjuvant chemotherapy and doing well with no recurrence after 1 year of follow-up. In conclusion, SCC of the ampulla is an unusual pathology that should be kept as a differential diagnosis for periampullary tumours. Surgical treatment with curative intent should be performed whenever feasible even in the setting of bulky tumour to improve the outcome.